Perancangan Sepatu Memanfaatkan Limbah Kulit dan Denim dengan Teknik Ecoprint - Tamara, Qhawa (Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
The development of the youth fashion world continues to change over time. Teenagers tend to want to look attractive and be the center of attention. One of the things that this group pays attention to is footwear. Its main function is to protect the feet when doing activities, especially when outdoors. Over time, humans continue to perfect the shape of shoes so that various types and attractive models appear. Currently, shoes are starting to change their function as supporting appearance and can even show a person's social status. The author uses the Gustami design method which consists of three stages, including: exploration, design, and embodiment. Data collection was carried out through field surveys, interviews, literature studies, visual studies, comparative product studies and trials. The ecoprint technique on leather is used to enrich the product's visuals and increase its value. Denim as a supporting material because it has an attractive texture and visual and a strong character so that it creates an aesthetic impression in a pair of shoes. The results of this design are shoes made of denim and leather waste that have been visually processed using the ecoprint technique. use of chemicals and In addition, the use of this technique and material aims to reduce pollution and environmental damage due to hazardous substances. The design of this shoe considers aspects of function, aesthetics, materials, and techniques so that it has more value. It is hoped that this product can provide inspiration for craft industry players and the community to innovate and develop sustainable products